Prevalence and Predictors of Persistent Human Immunodeficiency Virus Viremia and Viral Rebound After Universal Test and Treat: A Population-Based Study - Grabowski, M. Kate; Patel, Eshan U.; Nakigozi, Gertrude; Ssempijja, Victor; Ssekubugu, Robert; Ssekasanvu, Joseph; Ndyanabo, Anthony; Kigozi, Godfrey; Nalugoda, Fred; Gray, Ronald H.; Kalibbala, Sarah; Serwadda, David M.; et al. (The Journal of infectious diseases, 2021)
UNAIDS targets for human immunodeficiency virus (HIV) epidemic control by 2030 include that 86% of all HIV-positive persons be on antiretroviral therapy (ART) and achieve HIV viral load (VL) suppression [1]. The major policy initiative underpinning this target is universal test and treat (UTT), whereby all HIV-positive persons, irrespective of CD4 count or severity of illness, are immediately prescribed ART [2]. In sub-Saharan Africa, which accounts for more than half of all new HIV diagnoses globally, there has been considerable progress in increasing ART coverage [
Keywords: Africa; Cohort studies; HIV prevention; Universal test and treat; Viral suppression